STUDI KOMPARASI POLA PENULISAN BERITA FEATURE PADA MEDIA ONLINE LIPUTAN6.COM DAN TRIBUNSUMSEL.COM - Fitria Fitria; Hamidah Hamidah; Anang Walian (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2020)
ABSTRACK News writing can be conveyed in various types of writing, depending on what style the journalist or media wants to apply. These various styles of information delivery lead to various types of news, one of which is feature news. The existence of feature news is used as a media as a distraction for readers after reading hard news. In addition, the function of a media is not only to provide information for readers but also as a means of entertaining the audience, so that the features should be present to please and inspire readers. Therefore, researchers are interested in raising the title,